2007
DOI: 10.1111/j.1365-2958.2007.05947.x
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of fatty acid metabolism in bacteria

Abstract: SummaryIn Escherichia coli, the main player in transcription regulation of fatty acid metabolism is the FadR protein, which is involved in negative regulation of fatty acid degradation and in positive and negative regulation of the cellular processes related to it, as well as in positive regulation of the biosynthesis of unsaturated fatty acids in a concerted manner with negative regulation of FabR. On the other hand, Bacillus subtilis possesses two global transcriptional regulators, FadR (YsiA) and FapR. B. s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
348
0
6

Year Published

2009
2009
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 387 publications
(360 citation statements)
references
References 75 publications
(119 reference statements)
6
348
0
6
Order By: Relevance
“…Degradation of fatty acids under aerobic conditions in E. coli is carried out by the FadBA enzyme complex, a tetramer made up of proteins encoded by fadB and fadA (68,69), as part of the fadR regulon (70). fadB and fadA are highly conserved throughout both Gram-positive and Gram-negative bacteria (71), and both genes are present in all of the 8 species in our study set, with the exception of S. boydii, where fadB is annotated as a truncated pseudogene containing a frameshift (30). By correcting the frameshift, SearchDOGS was able to automatically predict a full-length (738-amino-acid) FadB protein showing very high sequence similarity to its annotated orthologs (Fig.…”
Section: Generation Of Resultsmentioning
confidence: 99%
“…Degradation of fatty acids under aerobic conditions in E. coli is carried out by the FadBA enzyme complex, a tetramer made up of proteins encoded by fadB and fadA (68,69), as part of the fadR regulon (70). fadB and fadA are highly conserved throughout both Gram-positive and Gram-negative bacteria (71), and both genes are present in all of the 8 species in our study set, with the exception of S. boydii, where fadB is annotated as a truncated pseudogene containing a frameshift (30). By correcting the frameshift, SearchDOGS was able to automatically predict a full-length (738-amino-acid) FadB protein showing very high sequence similarity to its annotated orthologs (Fig.…”
Section: Generation Of Resultsmentioning
confidence: 99%
“…25,49) Besides, the amyE gene encoding the extracellular -amylase hydrolyzing starch, 3,5) and the levDEFG-sacC operon encoding a fructose-specific phosphotransferase system and the extracellular levanase hydrolyzing fructose polymers and sucrose, 59,104) are also known to be subject to CcpA-mediated CCR. In addition, some members (lcfA-fadR-fadB-etfAB, fadNAE, and lcfB) of the FadR (formerly YsiA) regulon involved in fatty acid degradation 44,105) are under CcpA-dependent CCR (H. Matsuoka, and Y. Fujita, unpublished observation).…”
Section: Metabolic Network Mediated By Ccpamentioning
confidence: 99%
“…For the four enzymes directly involved in fatty acid biosynthesis, FabI, FabF, FabHA, and FabHB, Hutter et al previously reported induction of transcription by fatty acid biosynthesis inhibitors cerulenin and triclosan (13). Malonyl-CoA sterically inhibits FapR (9). It can be expected that this precursor of fatty acid biosynthesis accumulates upon fatty acid biosynthesis inhibition, causing derepression of the fatty acid biosynthesis enzymes.…”
Section: Discussionmentioning
confidence: 99%
“…Platensimycin as well as cerulenin, discovered in the 1960s, inhibit the 3-oxoacyl-acyl carrier protein (ACP) synthase II FabF (21,32), whereas platencin inhibits both FabF and 3-oxoacyl-ACP synthases III FabHA and FabHB (15,31). These enzymes catalyze the initial condensation of acyl-ACPs and existing fatty acid chains with malonyl-ACP, respectively (9). In contrast, triclosan, another fatty acid biosynthesis inhibitor, discovered in the 1970s, targets the second reduction step in the fatty acid chain elongating biosynthesis cycle, inhibiting the enoyl-ACP reductase FabI (11) (see Fig.…”
mentioning
confidence: 99%